A Scoping Review of Patient Readiness for Health-Illness Transition and Its Affect on Cancer Treatment Success - Nuzulullail, Agung Subakti; Aulawi, Khudazi; Hartini, Sri; Puspitasari, Halfie Zaqiyah Gusti; Irawan, Dana Prayoga (Media Publikasi Cendekia Indonesia, 2025)
Cancer survivors undergo a health-illness transition (HITs) from diagnosis to survivorship phase, which affects their quality of life and treatment. This study aims to determine the extent of readiness for the HITs transition among cancer survivors through a scoping review method based on the Arksey and O'Malley framework. We searched the ScienceDirect, PubMed, SpringerLink, and Wiley databases for studies addressing cancer patients and transition readiness in oncology care settings. The inclusion criteria were the ones that met the original English-language articles published between 2020 and 2024. Review articles, study protocols, and books were excluded. The screening procedure adhered to PRISMA 2020 guidelines, and article eligibility was assessed by three researchers using the JBI Critical Appraisal Checklist (2020). Ten articles were acquired, indicating that the majority of survivors had low to medium levels of transition readiness, particularly throughout the treatment and survivorship phases. This readiness is affected by support from family, peers, and healthcare professionals, along with several individual factors, including age, length of diagnosis, insurance status, patient competence, physical and emotional condition, cancer stage, treatment status, and access to health services and information. These results affirm that readiness for the HITs requires attention by providing appropriate support and strengthening individual factors. Future studies are expected to evaluate transition readiness from the diagnosis phase to enhance the integration and optimization of the care process, hence improving the overall quality of life for cancer survivors.